How to build successful business relationships - Kay, Frances 1949- (The Institution of Engineering and Technology, 2009)
The book has 10 chapters. The following topics are dealt with: business relationships; people networking; new business challenges; business communication; people management; team working; referrals; personnel rewards; and strategic planning. An index is also given.